Security Analysis of Quantization Schemes for Channel-based Key Extraction - Zenger, Christian; Zimmer, Jan; Paar, Christof (EAI Endorsed Transactions on Security and Safety, 2015)
The use of reciprocal and random properties of wireless channels for the generation of secret keys is a highly attractive option for many applications that operate in a mobile environment. In recent years, several practice-oriented protocols have been proposed, but unfortunately without a sufficient and consistent security analysis and without a fair comparison between each other. This can be attributed to the fact that until now neither a common evaluation basis, nor a security metric in an on-line scenario (e.g., with changing channel properties) was proposed. We attempt to close this gap by presenting test vectors based on a large measurement campaign, an extensive comparative evaluation framework (including ten protocols as well as new on-line entropy estimators), and a rigorous experimental security analysis. Further, we answer for the first time a variety of security and performance related questions about the behavior of 10 channel-based key establishment schemes from the literature.